Mechanical Behaviour of Alkali-Treated Fabric-Reinforced Polymer Matrix Composites - M. D. Mohan Gift; Shivkumar Mantri; Surakasi Raviteja; M. L. Rinawa; Dhiren Ramanbhai Patel; V. Nagaraju; A. H. Seikh; Sohail M. A. Khan; David Christopher (Advances in Polymer Technology)
Polyethylene (PE) was used as a composite material to create a fabric containing 40% pineapple, 30% jute, and 30% cotton fibres by weight. The physical characterisation is carried out, like deterioration and water absorption tests. PE-based composites were shown to have a lower water absorption rate when dipped in deionized water to perform an absorption test. Fabric/PE composites decomposed slowly in the soil during the degradation test. Alkali solution of 5 percent, 7 percent, and 9 percent sodium hydroxide by weight for 60 minutes was studied as alkali impact mechanical characteristics: mechanical testing’s like tensile strength and modulus, elongation at break, bending strength, and modulus. Data investigation exposed that the tensile strength and modulus, elongation at break, bending strength, and composite modulus values were 64 MPa and 871 MPa, 23.14 percent, 45 MPa, and 512 MPa. There were tensile strength and modulus, elongation at break, bending strength, and modulus of the neat polyethylene sheet that were 32Mpa and 342 MPa, 79 percent, 22 MPa, and 234 MPa, respectively. Compared to a polyethylene sheet, composite values for tensile strength and modulus, bending strength, and modulus raised by 107%, 156%, 110%, and 115% as a result of fabric reinforcing.